Palichnology of the Lower Devonian Wapske Formation, Perth-Andover-Mount Carleton region, northwestern New Brunswick, eastern Canada - Han, Yaojun; Pickerill, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1994)
The Lower Devonian Wapske Formation of the Tobique Group in the Perth-Andover-Mount Carleton region of north western New Brunswick forms part of the tcctonostratigraphic Tobique Zone. In this region, the formation is 4000 to 9000 m thick and is interpreted as deep-marine turbiditic in origin. Seven sedimentary facies are recognized. These are: conglomerate facies (Facies 1); massive and parallel-laminated sandstone facies (Facies 2); thin- to thick-bedded sandstone with minor mudstone interbeds and/or mud-capped facies (Facies 3); thin-bedded sandstone and mudstone facies (Facies 4); thin-bed ded, graded, fine-grained sandstone facies (Facies S); thin-bedded, fine-grained sandstone and silty mudstone facies (Facies 6); and thin- and medium-bedded siltstone and mudstone facies (Facies 7). These facies are grouped into five facies associa tions reflecting a deep-marine fan system consisting of distributary channels, depositions) lobes, lobe or fan fringes, and intcrchannel areas associated with a basin plain. A relatively diverse and well-preserved ichnofauna, consisting of 23 ichnogenera (41 ichnospecies) and three vernacular ichnotaxa, is systematically described, these comprising Arthraria Billings, 1872; Bergaueria Prantl, 1945; Chondrites von Sternberg, 1833; Cochlichnus Hitchcock, 18S8; Cosmorhaphe Fuchs, 1895; Cruziana d'Orbigny, 1842; Dendrotichnium Hantzschel, 1975; Didymautichnus Young, 1972, Helminthoida SchafhButl, 1851; Helminthopsis User, 1877; Hormosiroidea Schaffer, 1928; Monomorphichnus Crimes, 1970; Neonereites Scilacher, 1960; Palaeophycus Hall, 1847; Paleodictyon Meneghini in Murchison, 1850; Phycodes Richter, 1850; Protopaleodictyon Ksiqzkiewicz, 1970; Protavirgularia M'Coy, 1850; Rusophycus Hall, 1852; Skolithos Haldeman, 1840; Taenidium Heer, 1877; Uchirites Macsotay, 1967; Umfolozia Savage, 1971; two track forms and indeterminate scratch markings. Their palacoenvironmental distribution within the se quence correlates well with the interpreted submarine fan complex and compares favourably with other previously docu mented ichnofaunas from deep-marine fans. Collectively, the ichnofauna of the Wapske Formation is characteristic of Seilachcr's (1967) Nereites ichnofacies.